Pemeriksaan Kesehatan, Pemberian Bahan Makanan Bernutrisi pada Lansia dan ODGJ di Wanasara Tabanan - Kadek Sri Ariyanti; Cokorda Istri Mita Pemayun; Made Dewi Sariyani; Ni Made Indra Peratiwi (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2023)
Elderly and Mental illness who live in the UPTD Social Services and Protection of Women and Children Wanasara Tabanan are under the auspices of the Tabanan District Social Service. The need for nutritious food for Mental illness and the elderly is quite high, so they need contributions in the form of nutritious food ingredients to meet their nutritional needs. They also do not get regular health checks. This activity was carried out with the aim of conducting health screening and helping to meet the nutritional needs of the elderly and Mental illness. Activities carried out as an effort to solve the problem include checking blood pressure, blood sugar, cholesterol, uric acid and providing nutritious food ingredients to meet the nutritional needs of the elderly and people with mental illness. The targets in this activity are the elderly and Mental illness. There are 8 (eight) elderly people and 16 (sixteen) people with ODGJ. The results of the medical examination showed that blood pressure, blood sugar, uric acid and cholesterol were within normal limits. There are 2 (two) elderly people who have hypertension and have undergone routine treatment. This community service activity has good potential to improve the nutritional status and health status of the elderly and Mental illness. Routine health checks for Mental illness and the elderly are carried out as an effort to detect early chronic diseases that can be suffered by the elderly and Mental illness. Fulfillment of nutrition in the elderly and Mental illness can improve their nutritional status and health status ABSTRAK                  Lansia dan ODGJ yang tinggal di UPTD Pelayanan Sosial dan Perlindungan Perempuan dan Anak Wanasara Tabanan berada di bawah naungan Dinas Sosial Kabupaten Tabanan. Kebutuhan makanan bernutrisi ODGJ dan Lansia cukup tinggi, sehingga memerlukan sumbangsih berupa bahan makanan bernutrisi untuk memenuhi kebutuhan gizinya. Mereka juga tidak mendapatkan pemeriksaan kesehatan secara rutin. Kegiatan ini dilakukan dengan tujuan untuk melakukan skrining kesehatan dan membantu memenuhi kebutuhan gizi Lansia dan ODGJ.  Kegiatan yang dilakukan sebagai upaya pemecahan masalah antara lain pemeriksaan tekanan darah, gula darah, kolesterol, asam urat dan pemberian bahan makanan bernutrisi untuk memenuhi kebutuhan gizi lansia dan ODGJ. Sasaran dalam kegiatan ini adalah Lansia dan ODGJ. Jumlah Lansia ada 8 (delapan) orang dan ODGJ sebanyak 16 (enam belas) orang.  Hasil pemeriksaan kesehatan menunjukkan tekanan darah, gula darah, asam urat dan kolesterol dalam batas normal. Terdapat 2 (dua) orang lansia yang mengalami hipertensi dan sudah menjalani pengobatan rutin. Kegiatan pengabdian kepada masyarakat ini memiliki potensi yang baik untuk meningkatkan status gizi dan derajat kesehatan Lansia dan ODGJ. Pemeriksaan kesehatan secara rutin pada ODGJ dan Lansia dilakukan sebagai upaya deteksi dini penyakit kronis yang dapat diderita oleh Lansia dan ODGJ.  Pemenuhan nutrisi pada Lansia dan ODGJ dapat meningkatkan status gizi dan derajat kesehatannya.